Blockchain and the Personal Data Protection Act 2010 (PDPA) in Malaysia - Baskaran H.; Yussof S.; Rahim F.A.; Bakar A.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Blockchain; Digital storage; Data integrity; Decentralized architecture; European union; General data protection regulations; Malaysia; Privacy law; Data privacy